GAMBARAN STATUS GIZI PASIEN DIABETES MELITUS TIPE 2 DI BANGSAL PENYAKIT DALAM RSUD ARIFIN ACHMAD PROVINSI RIAU - ", Suryani; Rosdiana, Dani; Christianto, Erwin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTType 2 diabetes mellitus is caused by many factors which is characterized by chronic hyperglicemic resulting from defects in insulin secretion, insulin action, or both. The prevalence of diabetes mellitus in Indonesia was increase from previous years. It was caused by demographic factor and westernized lifestyle. The aim of this study is to find the description of nutritional status of type 2 diabetes mellitus patients in internal medicine ward in RSUD Arifin Achmad Provinsi Riau. This is a descriptive study with cross sectional approach with 30 respondents. Nutritional status was assessed by measurement of body mass index, mid-upper arm circumference, and waist circumference. This study showed that 90% of respondents were 40-65 years old with 36,7% male and 63,3% female. Nutritional status based on body mass index, many respondents were obesity grade I (33,3 %), 30 % of respondents were normal, 20% were overweight, 13,3% were underweight and 13,3% were obesity grade II. Based on mid-upper arm circumference, 40% of respondents were CED and 60% without CED. Based on waist circumference, 63,3% of respondents were central obesity and 36,7% were normal.Key words : Type 2 diabetes mellitus, nutritional status, body mass index, mid-upper arm circumference, waist circumference